GAMBARAN TINGKAT KECEMASAN KELUARGA PASIEN DAN PERAN PERAWAT ICU DI RSUD HAMBA MUARA BULIAN KABUPATEN BATANGHARI: GAMBARAN TINGKAT KECEMASAN KELUARGA PASIEN DAN PERAN PERAWAT ICU DI RSUD HAMBA MUARA BULIAN KABUPATEN BATANGHARI - safitri, yova (Media Husada Journal Of Nursing Science, 2024)
Family anxiety about critical patients being treated in the ICU will have an impact on the family. Nurses play a role in reducing the anxiety experienced by families by providing information about necessary treatment actions, information about the patient's condition, treatment plans and prognosis. The aim of this research is to determine the level of anxiety of the patient's family and the role of ICU nurses at Haji Abdoel Madjid Batoe Regional Hospital. This study used a quantitative descriptive research design, the research population was all families of patients treated in the ICU, a sample of 81 respondents. The sampling technique in this research used total sampling, and data analysis used univariate analysis. The instruments used in this research were questionnaires and HARS sheets. The results showed that 45.7% of respondents experienced moderate anxiety, 61.7% of respondents felt that the role of nurses was good. Most respondents' level of anxiety was on a medium scale (45.7%) and the ICU nurse's role was highest in disease prevention. The hospital should be able to create a counseling and education program to eliminate/reduce the anxiety of the patient's family.